Cmr1 enables efficient RNA and DNA interference of a III-B CRISPR–Cas system by binding to target RNA and crRNA. Issue 19 (5th September 2017) - Li, Yingjun; Zhang, Yan; Lin, Jinzhong; Pan, Saifu; Han, Wenyuan; Peng, Nan; Liang, Yun Xiang; She, Qunxin
Abstract: CRISPR–Cas (clustered regularly interspaced short palindromic repeats-CRISPR-associated) systems provide adaptive immunity against invasive nucleic acids guided by CRISPR RNAs (crRNAs) in archaea and bacteria. Type III CRISPR–Cas effector complexes show RNA cleavage and RNA-activated DNA cleavage activity, representing the only known system of dual nucleic acid interference. Here, we investigated the function of Cmr1 by genetic assays of DNA and RNA interference activity in the mutants and biochemical characterization of their mutated Cmr complexes. Three cmr1α mutants were constructed including ΔβΔ1α, Δβ1α-M1 and Δβ1α-M2 among which the last two mutants carried a double and a quadruple mutation in the first α-helix region of Cmr1α. Whereas the double mutation of Cmr1α (W58A and F59A) greatly influenced target RNA capture, the quadruple mutation almost abolished crRNA binding to Cmr1α. We found that Cmr2α-6α formed a stable core complex that is active in both RNA and DNA cleavage and that Cmr1α strongly enhances the basal activity of the core complex upon incorporation into the ribonucleoprotein complex. Therefore, Cmr1 functions as an integral activation module in III-B systems, and the unique occurrence of Cmr1 in III-B systems may reflect the adaptive evolution of type III CRISPR–Cas systems in thermophiles.